2009
DOI: 10.1080/09273940802596526
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Involvement in Sarcoidosis

Abstract: The most common ocular involvement in this study was both anterior and posterior segment involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 10 publications
0
20
0
2
Order By: Relevance
“…Fluorescein and indocyanine green angiography may demonstrate posterior segment activity such as choroidopathy, periphlebitis, and cystoid macular edema [3,82,83]. Studies using visual evoked potentials (VEPs) report abnormalities of the VEPs in sarcoid patients without ocular or neurologic symptoms, suggesting the value of VEPs in revealing subclinical involvement which can also help in the early diagnosis of neuro-ophthalmic sarcoidosis [84][85][86].…”
Section: Diagnostic Measuresmentioning
confidence: 99%
“…Fluorescein and indocyanine green angiography may demonstrate posterior segment activity such as choroidopathy, periphlebitis, and cystoid macular edema [3,82,83]. Studies using visual evoked potentials (VEPs) report abnormalities of the VEPs in sarcoid patients without ocular or neurologic symptoms, suggesting the value of VEPs in revealing subclinical involvement which can also help in the early diagnosis of neuro-ophthalmic sarcoidosis [84][85][86].…”
Section: Diagnostic Measuresmentioning
confidence: 99%
“…3 The severity of systemic involvement is not associated with the development of OS. 11,13,35,108 Only one study, to our knowledge, reports on a higher incidence of advanced stages of pulmonary sarcoidosis in patients with uveitis. 109 So far, there are no specific extraocular manifestations of sarcoidosis identified that show relationship with ocular involvement.…”
Section: Relation Between Ocular and Systemic Sarcoidosesmentioning
confidence: 99%
“…Eighty percent of patients have ocular Sarcoidosis manifest by anterior and posterior uveitis. (Atmaca, Atmaca-Sonmez et al 2009). This needs to be flagged in the pre-transplant clinic, as there is the added complication of steroid induced cataracts in the post-operative period.…”
Section: Lung Transplantation Workupmentioning
confidence: 99%